Pre-agreement assessment as a responsible lending tool in South Africa, the EU and Belgium: Part 1 - van Heerden, Corlia Maritha; Stteennot, Reinhard n/a (Potchefstroom Electronic Law Journal, 2018)
Responsible lending has become a very pertinent issue on the agenda of credit regulators across the globe who seek to combat the causes of consumer over-indebtedness. In this context the use of “pre-agreement assessment” as a tool to filter out those instances where, based on a consumer’s creditworthiness or ability to repay, credit should not be granted to such consumer, is a feature common to the lending regimes of various jurisdictions.This contributionÂ consists of two parts: PartÂ 1 provides a critical discussion of the reckless credit provisions of the National Credit Act 34 of 2005. PartÂ 2 detailsÂ the responsible lending measures contained in the EU Consumer Credit Directive and the EU Mortgage Credit Directive and providesÂ an appraisal of the responsible lending measures introduced by Belgium, being a jurisdiction that has always been very pro-active in the context of consumer credit protection.